2018
DOI: 10.1002/joc.5679
|View full text |Cite
|
Sign up to set email alerts
|

Recent recovery of surface wind speed in northwest China

Abstract: Previous studies have reported that much of the surface wind speed (SWS) over the mid-latitudes of the northern hemisphere has declined. However, very few studies have investigated the relatively recent phenomenon of wind recovery. Based on 68 wind data series, this paper examines changes in wind speed in northwest China between 1969 and 2015. In 1992, following a decade of sharply decreasing at a rate of 0.036 m s −1 a −1 (p < .05), the SWS began to significant increase at a rate of 0.004 m s −1 a −1 . The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 46 publications
4
48
1
Order By: Relevance
“…Our analyses of the relationship of the observed DMWS anomalies with three teleconnection indices with synoptic features concord with previous studies on mean wind speed (Gong and Ho 2003;Lin et al 2013;Y. Li et al 2018).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our analyses of the relationship of the observed DMWS anomalies with three teleconnection indices with synoptic features concord with previous studies on mean wind speed (Gong and Ho 2003;Lin et al 2013;Y. Li et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Despite the fact that no previous China DMWS study applied a homogenization method (Table 1), similar spatial patterns were found herein when compared to those regional studies (Wang et al 2015;Dong et al 2018). Moreover, significant (p , 0.05) changepoints were also detected in our DMWS series, which might be associated with the decadal variability of large-scale atmospheric circulation as previous studies stated (e.g., Azorin-Molina et al 2018b;Y. Li et al 2018).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This conclusion has been verified in many other studies (Achberger et al 2006;Dumitrescu et al 2014;Earl et al 2013;McVicar et al 2008;Minola et al 2016;Vautard et al 2010). Recent studies have found SWS recovery phenomena since the last decade over Saudi Arabia (Azorin-Molina et al 2018a), South Korea (Kim and Paik 2015), and China (Li et al 2018;Lin et al 2013). More details about global wind speed change in recent years can be found in the overviews of Wu et al (2018a) and Hartfield et al (2018).…”
Section: Introductionsupporting
confidence: 68%